2022
DOI: 10.3390/agronomy12051220
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungi Accelerate Leaf Physiological Activity and Resveratrol Accumulation in Polygonum cuspidatum by Up-Regulating Expression of Associated Genes

Abstract: Polygonum cuspidatum Sieb. et Zucc. is a major raw material for the extraction of drugs such as resveratrol, while the over-exploitation of P. cuspidatum decreases the yield and drug components. The purpose of this study was to analyze the effect of inoculation with root endophytic fungi Funneliformis mosseae and Piriformospora indica singly or in combination in biomass production, physiological activities (e.g., chlorophyll, soluble protein, and gas exchange) and main medicinal ingredients of P. cuspidatum, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The six genes associated with the synthesis of medicinal ingredients were screened in the NCBI database, and then Primer Premier 5.0 was used to design primer sequences ( Supplementary Table S1 ) for selected genes. qRT-PCR was conducted according to the protocol of Sun et al (2022b) . Each gene had three biological replicates, and each biological replicate contained three technical replicates.…”
Section: Methodsmentioning
confidence: 99%
“…The six genes associated with the synthesis of medicinal ingredients were screened in the NCBI database, and then Primer Premier 5.0 was used to design primer sequences ( Supplementary Table S1 ) for selected genes. qRT-PCR was conducted according to the protocol of Sun et al (2022b) . Each gene had three biological replicates, and each biological replicate contained three technical replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have reported that mycorrhizal MAPs such as liquorice ( Glycyrrhiza uralensis ) [ 40 ], pangola-grass Digitaria eriantha [ 39 ], and Polygonum cuspidatum [ 212 ] showed an increase in stomatal conductance, thereby increasing their photosynthetic rate. Indeed, it has been well demonstrated that water stress prompts stomatal closure, causing a reduction in CO 2 availability, which reduces photosynthesis in plants [ 100 ].…”
Section: Arbuscular Mycorrhizal Fungi Help Maps To Cope With Abiotic ...mentioning
confidence: 99%
“…S. indica can be successfully colonized in soybean roots, and the increase of Cd concentration in soil led to the decrease of soybean root colonization rate [12], which can be attributed to the toxicity of Cd to soybean improves the immunity of soybean under stress.…”
Section: S Indica Can Improve Soybean Growth Under CD Stressmentioning
confidence: 99%
“…Besides, the antioxidant defense system of the plant can be enhanced by the fungus, which has a vital role in resistance against biotic and abiotic stresses [11]. S. indica can increase plant photosynthesis, such as leaf transpiration rate and net photosynthetic rate, and improve antioxidant defense capabilities, such as proline and glutathione content to promote plant growth to resist Cd stress [12,13]. S. indica can not only increase soil urease and phosphatase activities to improve plant utilization efficiency of soil nutrients but also increase soil catalase to relieve the toxic effects of hydrogen peroxide [14].…”
Section: Introductionmentioning
confidence: 99%